Vozel absurdov - Košir, Fedja (Urbani izziv, 2002)
Since it was built, the railway station in Ljubljana, a transport node or in new terms a travellers centre, is a problem non plus ultra. Its rationale is multi-layered. To understand them it is necessary to analyse its concept (which we adhere to so tightly, that is senseless), the city's transport system as a whole and finally the programme, which has to be dealt with exceptionally flexibly. The only logical and simple solution is in fact only one that relinquishes the plan of the square and other surfaces on the level of the tracks to the pedestrian.
Keywords: Ljubljana; promet; prometna ureditev; železniške postaje; železniški promet